Method for Manufacturing Silicon Composite Anode Material for Secondary Battery Comprising Structure in which The Outer Surface of Hollow Granule is Covered with Carbon Nanomaterial

KR1020260132268APending Publication Date: 2026-09-02CBBS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
KR1020250024931
Authority / Receiving Office
KR · KR
Patent Type
Applications
Current Assignee / Owner
Filing Date
2025-02-26
Publication Date
2026-09-02

Smart Images

  • Figure PAT00001_ABST
    Figure PAT00001_ABST
Patent Text Reader

Abstract

According to the method for manufacturing a silicon composite negative electrode for a secondary battery comprising a structure in which the outer surface of a hollow structure granule of the present invention is coated with a carbon nanomaterial, the method comprises: a first spray solution preparation step of preparing a first spray solution by adding and stirring a binder polymer and nanosilicon to a mixed solvent containing two or more organic solvents; a first drying step of obtaining a hollow structure spherical powder in which the nanosilicon particles are aggregated by spraying and drying the first spray solution; a second spray solution preparation step of preparing a second spray solution by stirring the spherical powder and a commercial carbon source; and a second drying step of obtaining a hollow structure spherical powder composite by spraying and drying the second spray solution.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present invention relates to a method for manufacturing a silicon composite negative electrode for a secondary battery comprising a structure in which the outer surface of hollow structure granules is coated with carbon nanomaterial. Background Technology

[0003] Rechargeable batteries have established themselves as an essential technology in various industries, such as electric vehicles (EVs), energy storage systems (ESS), and portable electronic devices, serving as eco-friendly energy storage devices. Currently, graphite is primarily used as the anode material in commercially available rechargeable batteries, and graphite is classified into natural graphite and artificial graphite. However, graphite has limitations in meeting the demands for high-capacity batteries due to its structural characteristics and low theoretical capacity (372 mAh / g). In particular, natural graphite suffers from low structural stability due to volume expansion during long-term use, while artificial graphite requires high costs due to complex manufacturing processes, such as high-temperature heat treatment. Accordingly, the development of next-generation anode materials capable of replacing graphite is essential.

[0004] Silicon is attracting attention as a next-generation anode material capable of providing more than 10 times the storage capacity of graphite, with a theoretical capacity of over 4200 mAh / g. In particular, silicon possesses high energy density and fast charge / discharge characteristics, and is expected to play an important role in the market requiring high-capacity lithium-ion batteries.

[0005] Accordingly, the silicon anode market is showing rapid growth and is projected to account for 10.1% of the total anode market by around 2027. Furthermore, the market size is expected to exceed 20 trillion won by 2030, and it is evaluated as a material with high potential to replace existing graphite-based anodes.

[0006] However, silicon anode materials undergo repeated volume expansion of more than 300% during the charge and discharge process, which generates high mechanical stress and causes problems such as cracking, collapse of the electrode structure, detachment from the current collector, and blockage of the charge transfer path.

[0007] Due to these issues, the commercialization of silicon anode materials is being delayed, and various technological approaches are being taken to resolve this.

[0008] First, there is a method to reduce mechanical stress caused by volume expansion by reducing the size of silicon particles to the nanometer (nm) level. Silicon particles with a size of approximately 150 nm or less have been reported to have low mechanical stress, which reduces breakage during the charging and discharging process; however, the industry points out that there is still a high possibility of breakage occurring with increasing cycles. In addition, toxic substances such as silane (SiH4) gas are used in the manufacturing of nano-silicon, which can lead to environmental problems.

[0009] Another method involves suppressing volume expansion by composites of silicon with silica (SiO2) or graphite-based carbon materials. While silica offers high chemical and mechanical stability, it requires a high-temperature vacuum process for composite formation, and the low silicon ratio limits the capacity increase effect. Additionally, silica causes irreversible reactions with the electrolyte, leading to low initial efficiency. On the other hand, carbon-silicon composites exhibit high initial efficiency but suffer from low cycle life stability due to a lack of structural robustness.

[0010] In addition, there is the development of silicon anode materials based on carbon composites. Research is being conducted on technologies that composite silicon with various commercial carbon sources (graphite, expanded graphite, graphene, CNT, fullerene, carbon black, etc.). However, research on selecting the optimal carbon material is still ongoing, and there is a need to develop an optimized composite structure that can effectively suppress the volume expansion of silicon.

[0011] Currently, silicon anode materials are used by adding them to existing graphite anode materials at a weight ratio of less than 10%, and it is difficult to increase the silicon ratio due to the high volume expansion of silicon. Therefore, for the practical application of silicon-based anode materials, there is a need to develop technology that can increase the silicon usage ratio while improving initial capacity and simultaneously enhancing cycle efficiency and initial efficiency. The problem to be solved

[0013] The objective of the present invention, devised to solve the problems described above, is to provide a method for manufacturing a silicon composite negative electrode for a secondary battery comprising a structure in which the outer surface of a hollow structure granule is coated with a carbon nanomaterial, which can produce a silicon composite negative electrode for a secondary battery comprising a structure in which the outer surface of a stable hollow structure granule with high sphericity and uniformity is coated with a carbon nanomaterial, thereby enabling high cycle efficiency by suppressing the cracking phenomenon of spherical powder, i.e., silicon, with low mechanical stress during volume expansion, and enabling fast charging speed by optimizing the electron movement path during charging and discharging by forming a uniform conductive network. means of solving the problem

[0015] According to the method for manufacturing a silicon composite negative electrode for a secondary battery comprising a structure in which the outer surface of a hollow structure granule is coated with a carbon nanomaterial to achieve the above-mentioned purpose, the method comprises: a first spray solution preparation step of preparing a first spray solution by adding and stirring a binder polymer and nanosilicon in a mixed solvent containing two or more organic solvents; a first drying step of obtaining a hollow structure spherical powder in which the nanosilicon particles are aggregated by spraying and drying the first spray solution; a second spray solution preparation step of preparing a second spray solution by stirring the spherical powder and a commercial carbon source; and a second drying step of obtaining a hollow structure spherical powder composite by spraying and drying the second spray solution.

[0016] In addition, a method for manufacturing a silicon composite negative electrode for a secondary battery comprising a structure in which the outer surface of the hollow structure granules is coated with a carbon nanomaterial further comprises a heat treatment step of heat-treating the spherical powder composite in an inert atmosphere; and the first spray liquid manufacturing step comprises a mixed solvent manufacturing step of manufacturing a mixed solvent comprising two or more organic solvents, a first stirring step of adding and stirring nanosilicon to the mixed solvent, and a second stirring step of adding and stirring a binder polymer after the first stirring step.

[0017] In addition, the above mixed solvent comprises a first organic solvent comprising one or more of NMP (N-Methyl-2-pyrrolidone), DMSO (Dimethyl sulfoxide), DMF (Dimethylformamide), and THF (Tetrahydrofuran), and a second organic solvent comprising one or more of ethanol, methanol, and acetic acid.

[0018] In addition, the mixed solvent comprises a first organic solvent having a first boiling point and a second organic solvent having a second boiling point lower than the first boiling point.

[0019] In addition, the above mixed solvent is characterized by the first organic solvent and the second organic solvent being mixed in a mass ratio of 10:1 to 2:1.

[0020] In addition, the binder polymer is characterized by being in an amount of 1 to 5 parts by weight per 100 parts by weight of the mixed solvent.

[0021] In addition, the nanosilicon is characterized by being in an amount of 1 to 7 parts by weight per 100 parts by weight of the mixed solvent.

[0022] In addition, the nanosilicon is characterized by having a size of 0.1 to 0.7 μm.

[0023] In addition, the above commercial carbon source includes one or more of natural graphite, artificial graphite, carbon black, acetylene black, GIC (Graphite Intercalated Compound), expanded graphite, activated carbon, graphite nanoplatelets (GNP), and carbon nanotubes (CNT).

[0024] In addition, the above commercial carbon source is a carbon aqueous solution containing one or more carbons, and 100 parts by weight of the carbon aqueous solution contains 0.5 to 1.5 parts by weight of one or more carbons, and the spherical powder is characterized in that it is 4 to 6 parts by weight with respect to 100 parts by weight of the carbon aqueous solution.

[0025] In addition, the heat treatment step is characterized by heat treating for 2 to 4 hours in an inert atmosphere at 600 to 800°C. Effects of the invention

[0027] The effects of the present invention as described above allow for the suppression of cracking of spherical powder, i.e., silicon, due to low mechanical stress during volume expansion, thereby enabling high cycle efficiency. Furthermore, by forming a uniform conductive network to optimize the electron transport path during charging and discharging, a silicon composite negative electrode for a secondary battery can be manufactured by coating the outer surface of highly spherical, uniform, and stable hollow granules with carbon nanomaterials, thereby enabling fast charging speeds. This provides a method for manufacturing a silicon composite negative electrode for a secondary battery comprising a structure in which the outer surface of hollow granules is coated with carbon nanomaterials. Of course, the scope of the present disclosure is not limited by these effects. Brief explanation of the drawing

[0029] FIG. 1 is a flowchart illustrating a method for manufacturing a silicon composite negative electrode for a secondary battery, comprising a structure in which the outer surface of a hollow structure granule is coated with a carbon nanomaterial according to a preferred embodiment of the present invention. FIG. 2 is a flowchart illustrating in more detail a method for manufacturing a silicon composite negative electrode for a secondary battery, comprising a structure in which the outer surface of hollow structure granules is coated with carbon nanomaterials according to a preferred embodiment of the present invention. FIG. 3 is an enlarged view of a spherical powder of a method for manufacturing a silicon composite negative electrode for a secondary battery, comprising a structure in which the outer surface of a hollow structure granule is coated with a carbon nanomaterial according to a preferred embodiment of the present invention. FIG. 4 is a diagram showing the hollow structure of a spherical powder in a method for manufacturing a silicon composite negative electrode material for a secondary battery, comprising a structure in which the outer surface of a hollow structure granule is coated with a carbon nanomaterial according to a preferred embodiment of the present invention. FIG. 5 is a drawing showing a silicon composite negative electrode for a secondary battery having a structure in which the outer surface of a hollow structure granule is coated with a carbon nanomaterial, manufactured by a method for manufacturing a silicon composite negative electrode for a secondary battery having a structure in which the outer surface of a hollow structure granule is coated with a carbon nanomaterial according to a preferred embodiment of the present invention. Specific details for implementing the invention

[0030] The advantages and features of the present invention and the methods for achieving them will become clear by referring to the embodiments described below in detail together with the accompanying drawings. However, the present invention is not limited to the embodiments disclosed below but may be implemented in various different forms. These embodiments are provided merely to ensure that the disclosure of the present invention is complete and to fully inform those skilled in the art of the scope of the invention, and the present invention is defined only by the scope of the claims. Throughout the specification, the same reference numerals refer to the same components.

[0031] In the following embodiments, terms such as first, second, etc. are used not in a limiting sense, but for the purpose of distinguishing one component from another component.

[0032] In the following examples, singular expressions include plural expressions unless the context clearly indicates otherwise.

[0033] In the following embodiments, terms such as "include" or "have" mean that the features or components described in the specification are present, and do not preclude the possibility that one or more other features or components may be added.

[0034] In the following embodiments, when a part such as a layer, region, or component is described as being on or above another part, it includes not only cases where it is directly on top of another part, but also cases where another region, component, etc. is interposed in between.

[0035] In the drawings, the size of components may be exaggerated or reduced for convenience of explanation. For example, the size and thickness of each component shown in the drawings are depicted arbitrarily for convenience of explanation, and therefore the present disclosure is not necessarily limited to what is depicted.

[0036] In this specification, “A and / or B” indicates the case where it is A, B, or A and B. And, “at least one of A and B indicates the case where it is A, B, or A and B.”

[0037] In the following embodiments, when layers, regions, components, etc. are described as being connected, this includes cases where the layers, regions, components are directly connected, or / or cases where other layers, regions, components are interposed between the layers, regions, components to form an indirect connection. For example, when layers, regions, components, etc. are described as being electrically connected in this specification, it indicates cases where the layers, regions, components, etc. are directly electrically connected, and / or cases where other layers, regions, components, etc. are interposed between them to form an indirect electrical connection.

[0038] Where in this specification a quantity, concentration, or other value or parameter is given as an enumeration of a range, a preferred range, a preferred upper limit, and a preferred lower limit, it should be understood that any pair of any upper range limit or preferred value and any lower range limit or preferred value, regardless of whether the range is disclosed separately, specifically discloses any range that may be formed. Where a range of numerical values ​​is mentioned in this specification, unless otherwise stated, for example, without limiting terms such as greater than or less than, the range is intended to include its endpoint value and all integers and fractions within that range. The scope of the invention is not intended to be limited to the specific value mentioned when defining the range.

[0039] Among the physical properties mentioned in this specification, if the measured temperature affects the property, the property is measured at room temperature unless specifically otherwise specified. The term "room temperature" refers to a natural temperature that has not been heated or cooled, and may mean, for example, any temperature within the range of about 10°C to 30°C, or a temperature of about 23°C or about 25°C. Furthermore, unless specifically otherwise specified, the unit of temperature in this specification is °C.

[0040] In addition, among the physical properties mentioned in this specification, if the measured pressure affects the physical property, unless otherwise specifically defined, the physical property is measured at normal pressure, that is, atmospheric pressure (about 1 atmosphere).

[0042] Hereinafter, the present invention will be described with reference to drawings illustrating a method for manufacturing a silicon composite negative electrode for a secondary battery comprising a structure in which the outer surface of a hollow structure granule is coated with a carbon nanomaterial according to embodiments of the present invention.

[0043] FIG. 1 is a flowchart illustrating a method for manufacturing a silicon composite negative electrode for a secondary battery, comprising a structure in which the outer surface of a hollow structure granule is coated with a carbon nanomaterial according to a preferred embodiment of the present invention.

[0044] Referring to FIG. 1, a method for manufacturing a silicon composite negative electrode for a secondary battery, comprising a structure in which the outer surface of a hollow structure granule according to the present invention is coated with a carbon nanomaterial, comprises a first spray liquid manufacturing step (S10), a first drying step (S20), a second spray liquid manufacturing step (S30), and a second drying step (S40).

[0045] First, the first spray solution manufacturing step (S10) can be performed by adding and stirring a binder polymer and nanosilicon to a mixed solvent containing two or more organic solvents to produce the first spray solution.

[0046] Here, the first spray liquid manufacturing step (S10) may include a mixed solvent manufacturing step, a first stirring step, and a second stirring step.

[0047] The mixed solvent preparation step can prepare a mixed solvent containing two or more organic solvents.

[0048] At this time, the mixed solvent may include a first organic solvent comprising one or more of NMP (N-Methyl-2-pyrrolidone), DMSO (Dimethyl sulfoxide), DMF (Dimethylformamide), and THF (Tetrahydrofuran), and a second organic solvent comprising one or more of ethanol, methanol, and acetic acid.

[0049] The first organic solvent may be an aphrotic solvent, and the second organic solvent may be a protic solvent, but is not limited thereto.

[0050] In other words, the mixed solvent can consist of a first organic solvent, which is an aphrotic solvent, and a second organic solvent, which is a protic solvent. Applying such a mixed solvent system can improve the performance of silicon composite anode materials for secondary batteries, which include a structure in which the outer surface of hollow granules is coated with carbon nanomaterials. This is because the two types of solvents play different roles, improving the dispersibility of the electrode active material and the homogeneity of the coating. The aphrotic solvent has low polarity and effectively disperses carbon-based materials, while the protic solvent has high polarity and helps the uniform dispersion of hydrophilic materials such as silicon. Using both solvents together creates an environment where silicon and carbon can be uniformly distributed, allowing the electrode coating layer to be formed more homogeneously. As a result, the active material within the electrode is evenly distributed, increasing the initial capacitance, and maintaining the stability of the electrode structure during the charging and discharging process.

[0054] In addition, the solvent may be selected based on solubility, volatility, and chemical reactivity for mixing. For example, the mixed solvent may include, but is not limited to, NMP of the first organic solvent and ethanol of the second organic solvent.

[0055] In addition, the mixed solvent contains two or more organic solvents so that the first spray liquid can form a hollow structure as it is dried after spraying in the first drying step (S20) described later.

[0056] The ability to form a hollow structure can be achieved by drying using the difference in boiling points.

[0057] That is, the mixed solvent preferably comprises a first organic solvent having a first boiling point and a second organic solvent having a second boiling point lower than the first boiling point, but is not limited thereto.

[0058] Specifically, the first organic solvent may have a relatively high affinity for solids (binder polymer, nanosilicon) and a relatively high boiling point. Additionally, the second organic solvent may have a relatively low solubility for solids and a relatively low boiling point. That is, the first organic solvent has a higher boiling point than the second organic solvent and evaporates slowly. Furthermore, the second organic solvent evaporates faster than the first organic solvent. More specifically, the first organic solvent, with its high boiling point, evaporates relatively slowly, which helps the active material to be evenly coated while the spherical powder is drying. On the other hand, the second organic solvent, with its low boiling point, evaporates quickly, which allows for appropriate control of the viscosity of the spherical powder and induces the formation of a uniform carbon layer. In other words, using both solvents together can prevent sudden deformation or cracking during the solvent removal process within the electrode, and consequently, an improvement in the homogeneity of the coating layer can be expected.

[0059] In addition, the mixed solvent may be formed by mixing the first organic solvent and the second organic solvent in a mass ratio of 10:1 to 2:1. In other examples, the mass ratio may be 9:1, 8:1, 7:1, 6:1, 5:1, 4:1, or 3:1, but is not limited thereto.

[0060] Here, if the ratio of the second organic solvent exceeds the range specified above, the second organic solvent rapidly disappears due to rapid evaporation, which may prevent the proper formation of the hollow structure. Excessively rapid drying causes internal shrinkage of the particles, preventing the formation of a hollow structure and increasing the likelihood of forming high-density solid particles.

[0061] In addition, if the ratio of the second organic solvent is lower than the range specified above, the first organic solvent increases, slowing down the evaporation rate, and the drying of the first spray liquid may not be properly carried out. This may cause particles to clump together during the first drying step (S20) described later, or cause the spray liquid to be discharged from the nozzle in an incompletely dried state during spraying, which may result in nozzle clogging.

[0062] Accordingly, as the first organic solvent and the second organic solvent described above are mixed in the mass ratio specified above, a hollow structure with an empty interior can be formed due to the rapid evaporation of the second organic solvent, and uniform spraying and drying can be achieved by controlling the evaporation rate of the first organic solvent.

[0063] The first stirring step may involve adding and stirring nanosilicon to the mixed solvent.

[0064] At this time, the nanosilicon may be 1 to 7 parts by weight per 100 parts by weight of the mixed solvent. In other examples, the nanosilicon may be 2 parts by weight or more, 3 parts by weight or more, or 4 parts by weight or more, or 6 parts by weight or less, 5 parts by weight or less, or 4 parts by weight or less, but is not limited thereto.

[0065] Here, if the nanosilicon content is less than the weight part specified above, the production yield may drop too low, and there is a possibility that the spherical powder composite described later will not be formed. Additionally, the nanosilicon content generated after spray drying may decrease, which could result in a lower energy density of the final electrode.

[0066] In addition, if the amount of nanosilicon exceeds the weight part specified above, the nanosilicon particles may clump together rather than being uniformly dispersed. Furthermore, during the spray drying process, the nanosilicon may not be evenly distributed within the spray droplet, and there is a possibility that nozzle clogging may occur due to the excessive concentration.

[0067] That is, by including nanosilicon in the weight range specified above with respect to 100 weight parts of the mixed solvent, uniform spraying of nanosilicon can be achieved, thereby enabling production yield and uniform particle formation.

[0068] In addition, the nanosilicon may have a size of 0.1 to 0.7 µm. In other examples, the size of the nanosilicon may be 0.2 or more or 0.3 µm or more, or 0.6 or less, 0.5 or less, or 0.4 µm or less, but is not limited thereto.

[0069] Here, if the size of the nanosilicon exceeds the range specified above, cracking of the silicon due to volume expansion may occur, and it is difficult to form a stable hollow structure cluster through spray drying. This is because, as the nanosilicon particles become larger, internal stress increases during expansion, causing structural cracking to occur more easily, which lowers the durability of the silicon electrode and reduces the cycle efficiency.

[0070] Furthermore, as the nanosilicon particles become larger, it becomes difficult to form a hollow structure. In other words, during spray drying, empty spaces are formed inside the nanosilicon particles due to the evaporation of the mixed solvent; however, if the nanosilicon particles are large, it is difficult to form these internal empty spaces uniformly.

[0071] In addition, if the size of the nanosilicon is less than the range specified above, a hollow structure is formed during the process of internal shrinkage as the mixed solvent evaporates, but it is difficult to create an empty space inside due to the small size of the nanosilicon particles. That is, only simple solid particles are formed, and spherical powder with a hollow structure may not be formed.

[0072] In addition, as the nanosilicon particles become smaller, their surface energy increases, causing them to clump together. Consequently, when spray-dried, they may not exist as individual particles but instead form aggregated, high-density particles that are clumped together.

[0073] Therefore, by forming nanosilicon within the size range specified above, spherical powder having a hollow structure can be easily manufactured without breakage during volume expansion, and electrode durability and performance can be improved.

[0074] In the second stirring step, a binder polymer can be added and stirred after the first stirring step.

[0075] At this time, the binder polymer may be 1 to 5 parts by weight per 100 parts by weight of the mixed solvent, preferably 3 parts by weight, but is not limited thereto.

[0076] Here, the binder polymer ensures that the nanosilicon particles are uniformly dispersed and do not aggregate.

[0077] If the binder polymer is less than 1 weight part, the nanosilicon particles may not be sprayed uniformly, and clusters may not be properly formed. In other words, it becomes difficult to form a hollow structure, and the electrode structure may become non-uniform.

[0078] In addition, if the binder polymer is 5 parts by weight or more, it can excessively surround the silicon particles, which can reduce conductivity within the electrode material and lower battery performance, such as capacitance and cycle efficiency.

[0079] Accordingly, as the binder polymer contains 1 to 5 parts by weight per 100 parts by weight of the mixed solvent, the nanosilicon can be uniformly aggregated to form a hollow structure and clusters of nanosilicon, thereby improving battery performance.

[0080] At this time, the binder polymer may be, for example, PVDF, PVA, CMC, or a combination of two or more of these, but is not limited thereto.

[0082] The first drying step (S20) can obtain a spherical powder with a hollow structure in which nanosilicon particles are aggregated by spraying and drying the first spray liquid.

[0083] At this time, the first spray liquid can form a hollow structure as it dries during spray drying. At this time, the hollow structure can be formed by a mixed solvent containing two or more organic solvents.

[0084] That is, the first organic solvent, nanosilicon, and binder polymer, which have a high affinity for solids, diffuse within the spray droplet of the first spray liquid and move toward the shell of the spray droplet. Then, the second organic solvent, which has a relatively low affinity for solids, is located in the core of the spray droplet. In this state, the first organic solvent and the second organic solvent evaporate, and as the spray droplet dries, spherical powder with a hollow structure having a diameter of several micrometers is formed, in which nanosilicons are aggregated.

[0085] The first organic solvent and the second organic solvent are organic solvents and have a lower surface tension than water, so when spray-dried, spherical powder that is closer to a sphere and smaller in size than the water-based spray liquid is formed as shown in Fig. 4.

[0086] In addition, the spherical powder is formed into a hollow structure as shown in Fig. 4. That is, the nanosilicon is formed into a hollow spherical powder due to the evaporation and drying of the organic solvent.

[0087] These hollow spherical powders contain a binder polymer, so the binder polymer can be carbonized by heat treatment.

[0088] The second spray liquid manufacturing step (S30) can manufacture the second spray liquid by stirring spherical powder and a commercial carbon source.

[0089] At this time, the hollow spherical powder formed through the first drying step (S20) maintains a hollow structure with an empty interior as shown in Fig. 4 and is used as a silicon electrode material.

[0090] In addition, a carbon coating is required to alleviate the expansion problem of spherical powder and improve electrical conductivity. At this time, a commercial carbon source can be dispersed to uniformly coat the surface of the spherical powder.

[0091] That is, the second spray liquid manufacturing step (S30) manufactures a second spray liquid that can be sprayed to coat the surface of spherical powder with a commercial carbon source.

[0092] Here, the commercial carbon source may include one or more of natural graphite, artificial graphite, carbon black, acetylene black, GIC (Graphite Intercalated Compound), expanded graphite, activated carbon, graphite nanoplatelets (GNP), or carbon nanotubes (CNT).

[0093] In order to coat a commercial carbon source onto the surface of a spherical powder, the commercial carbon source may consist of a carbon aqueous solution containing one or more carbons.

[0094] 100 parts by weight of the carbon aqueous solution may contain 0.5 to 1.5 parts by weight of one or more carbons, preferably 1 part by weight, but is not limited thereto.

[0095] At this time, if one or more carbons are 0.5 parts by weight or less, the carbons cannot effectively surround the spherical powders, and thus cannot effectively suppress the volume expansion of the spherical powders during charging and discharging, resulting in structural instability and the spherical powders breaking. In addition, since spherical powders have low electrical conductivity, if there is a lack of carbon, the conductive path between the spherical powders is severed, which may degrade electrical properties.

[0096] In addition, if one or more carbons are present in an amount of 1.5 parts by weight or more, the carbons may act to surround the spherical powder while simultaneously undergoing aggregation themselves, forming independent carbon entities. These carbon entities do not combine with the spherical powder and act as inert carbon materials within the electrode, which can degrade performance. That is, the uniformity of the silicon composite anode material for secondary batteries containing a structure in which the outer surface of hollow granules is coated with carbon nanomaterials may decrease, and battery performance may become unstable. Furthermore, if there is a high amount of carbon, it may be difficult for lithium to diffuse into the spherical powder, which could lead to a reduction in capacity and a decrease in charging and discharging speeds. Additionally, the density of the silicon composite anode material for secondary batteries containing a structure in which the outer surface of hollow granules is coated with carbon nanomaterials may decrease, resulting in inefficient use of space within the electrode and potentially reducing battery capacity.

[0097] Accordingly, 100 parts by weight of the carbon aqueous solution can improve the charging and discharging efficiency and durability of the battery by containing 0.5 to 1.5 parts by weight of one or more carbons, thereby enveloping the spherical powder to prevent it from breaking, improving conductivity, and facilitating lithium diffusion.

[0098] Meanwhile, the spherical powder may be 4 to 6 parts by weight per 100 parts by weight of the carbon aqueous solution, preferably 5 parts by weight, but is not limited thereto.

[0099] Specifically, 4 to 6 parts by weight of spherical powder may be included per 100 parts by weight of carbon aqueous solution.

[0100] Here, if the spherical powder is 4 parts by weight or less, the carbon aqueous solution increases, and the material distribution inside the spray droplet may become uneven when the second spray solution is sprayed. That is, if there are many carbon particles inside the spray droplet, the evaporation rate of the organic solvent is not constant, making it difficult to form a hollow structure. In addition, as the proportion of carbon becomes higher than that of nanosilicon, the proportion of active material in the electrode decreases, which may reduce the battery capacity.

[0101] In addition, if the amount of spherical powder is 6 parts by weight or more, the amount of carbon aqueous solution decreases, and the viscosity of the second spray solution increases, which may cause the nozzle to clog when the second spray solution is sprayed and prevents a uniform distribution of spray droplets.

[0102] The second drying step (S40) can obtain a hollow spherical powder composite by spraying and drying the second spray liquid.

[0103] At this time, the second spray solution may further include the aforementioned mixed solvent or organic solvent. This allows the carbon layer surrounding the spherical powder to be uniformly coated, i.e., fixed, as the organic solvent evaporates after the second spray solution is sprayed.

[0104] FIG. 2 is a flowchart illustrating in more detail a method for manufacturing a silicon composite negative electrode for a secondary battery, comprising a structure in which the outer surface of hollow structure granules is coated with carbon nanomaterials according to a preferred embodiment of the present invention.

[0105] Referring to FIG. 1, a method for manufacturing a silicon composite negative electrode for a secondary battery according to the present invention, comprising a structure in which the outer surface of a hollow structure granule is coated with a carbon nanomaterial, comprises a first spray liquid manufacturing step (S10), a first drying step (S20), a second spray liquid manufacturing step (S30), a second drying step (S40), and a heat treatment step (S50).

[0106] Since S10 to S40 of FIG. 2 are identical to those disclosed in FIG. 1, a detailed description will be omitted.

[0107] The heat treatment step (S50) is a step for stabilizing the carbon layer described above, in which the spherical powder composite is heat-treated in an inert atmosphere.

[0108] That is, the heat treatment step (S50) can increase the bonding strength with the spherical powder, so the expansion of the spherical powder can be suppressed. Accordingly, referring to FIG. 5, a silicon composite negative electrode material for a secondary battery can be seen that includes a structure in which the outer surface of the heat-treated hollow structure granules is coated with carbon nanomaterial.

[0109] Specifically, the heat treatment step (S50) can be performed in an inert atmosphere at 600 to 800°C for 2 to 4 hours.

[0110] That is, if heat treatment is performed at 600 to 800°C, the remaining organic components, such as binder polymer and organic solvent, are effectively carbonized, and a conductive carbon layer can be formed.

[0111] At this time, if the temperature is 600℃ or lower, carbonization of the organic components does not occur, and the carbon layer may be formed unevenly, and if the temperature is 800℃ or higher, mass loss may occur due to deterioration.

[0112] In addition, if the heat treatment time is 2 hours or less, carbonization may not be completely achieved and an uneven carbon layer may be formed, and if it is 4 hours or more, the strength may decrease due to deterioration.

[0113] As such, the manufactured spherical powder composite is formed with a small size of 10㎛ or less, which allows for the suppression of cracking of the spherical powder, i.e., silicon, due to low mechanical stress during volume expansion, thereby enabling high cycle efficiency. In addition, by forming a uniform conductive network to optimize the electron transport path during charging and discharging, a fast charging speed can be realized. Furthermore, by securing a particle shape with high sphericity and uniformity, the stability of the composite paste can be improved during the rolling process, which is essential in the secondary battery manufacturing process, thereby ensuring uniformity in electrode formation.

[0114] Meanwhile, the present invention has one objective of providing a silicon composite negative electrode for a secondary battery comprising a structure in which the outer surface of a hollow structure granule is coated with a carbon nanomaterial, manufactured by a method for manufacturing a silicon composite negative electrode for a secondary battery comprising a structure in which the outer surface of a hollow structure granule described above is coated with a carbon nanomaterial.

[0115] In addition, the silicon composite anode material for a secondary battery comprising a structure in which the outer surface of the hollow structure granules provided in the present invention is coated with a carbon nanomaterial may have an average particle size of 5 to 20 μm. The average particle size may be 7 or more or 9 μm or more, or 18 or less, 16 or less, or 14 μm or less, but is not limited thereto. When having an average particle size within the above range, uniform dispersion among particles within the electrode is induced, and the charge / discharge efficiency and cycle life of the silicon-based anode material can be improved.

[0116] Meanwhile, the present invention can provide a secondary battery comprising a silicon composite negative electrode material for a secondary battery, the structure comprising a structure in which the outer surface of the hollow structure granules manufactured above is coated with a carbon nanomaterial. The battery can be expected to significantly improve the driving range of a vehicle, shorten charging time, and extend the battery life.

[0118] The advantages and features of the present invention and the methods for achieving them will become clear by referring to the embodiments described below in detail together with the accompanying drawings. However, the present invention is not limited to the embodiments disclosed below but may be implemented in various different forms. These embodiments are provided merely to ensure that the disclosure of the present invention is complete and to fully inform those skilled in the art of the scope of the invention, and the present invention is defined only by the scope of the claims. Throughout the specification, the same reference numerals refer to the same components.

[0120] Hereinafter, the present invention will be described with reference to drawings illustrating a method for manufacturing a silicon composite negative electrode for a secondary battery comprising a structure in which the outer surface of a hollow structure granule is coated with a carbon nanomaterial according to embodiments of the present invention.

[0121] [Example 1]

[0122] First, silicon with a diameter of 1 µm is ground to a diameter of 0.3 µm using a ball mill or jet mill.

[0123] Then, a mixed solvent is prepared by mixing ethanol and NMP in a mass ratio of 4 to 1. Additionally, 3 wt% of a binder polymer is added to the mixed solvent and stirred. Then, 5 wt% of nanosilicon is added to the mixed solvent and stirred to prepare a first spray solution.

[0124] In addition, the first spray solution prepared is spray-dried to obtain a spherical powder with a hollow structure in which silicon nanoparticles are aggregated. The obtained spherical powder is added at 5 wt% to a 1 wt% graphene aqueous solution and stirred to prepare a second spray solution.

[0125] The manufactured second spray solution is spray-dried to obtain a hollow-structured spherical powder composite.

[0126] The spherical powder composite is heat-treated at 700°C in an inert atmosphere for 3 hours.

[0127] In this way, a method for manufacturing a silicon composite negative electrode for a secondary battery is manufactured, comprising a structure in which the outer surface of hollow structure granules is coated with carbon nanomaterial.

[0128] A method for manufacturing a silicon composite anode for a secondary battery, comprising a structure in which the outer surface of the finally manufactured hollow structure granules is coated with carbon nanomaterial, was confirmed to have a hollow structure and an electrode active material (commercial carbon) coated on the surface. The average particle size was measured to be approximately 8 to 12 μm.

[0130] [Comparative Example 1]

[0131] Comparative Example 1 is prepared by preparing the first spray solution of Example 1 using only ethanol, excluding NMP, instead of a mixed solvent.

[0133] [Comparative Example 2]

[0134] Comparative Example 2 is prepared by using water instead of the mixed solvent or organic solvent (ethanol, NMP) of Example 1 to prepare the first spray solution.

[0136] [Comparative Example 3]

[0137] Comparative Example 3 is prepared by heat-treating the hollow spherical powder obtained from the first spray solution of Example 1 (preparation of the second spray solution of Example 1 and spray drying of the second spray solution are omitted).

[0139] [Comparative Example 4]

[0140] Comparative Example 4 is prepared by preparing a hollow-structured spherical powder composite obtained from the second spray liquid of Example 1 (the heat treatment step of Example 1 is omitted).

[0142] [Comparative Example 5]

[0143] Comparative Example 5 is prepared by preparing the spherical powder composite of Example 1 with silicon with a diameter of 1 μm.

[0145] [Evaluation Example]

[0146] The composite cathode material of Example 1 and the cathode materials of Comparative Examples 1 to 5 were appropriately mixed with spheroidized graphite for cathode materials, and then an aqueous dispersion of the mixture was prepared by mixing it with an appropriate amount of water, a binder (SMC / CBR or PAA is suitable), and a conductive material (carbon black such as SuperP), and then coated onto a copper electrode plate. Subsequently, heat treatment was performed to ensure the mixture was firmly coated onto the copper electrode plate, and then stamped to produce a circular cathode electrode plate. In addition, a lithium chip was prepared as the anode plate, and a PE separator, a spacer, a coin cell container, a spring, and a gasket were prepared and combined to manufacture a coin cell. The capacitance (mAh / g) and cycle efficiency (200 cycles, %) of the manufactured coin cell were measured under 0.1C / 0.1C charge / discharge conditions at 25°C, and the results are shown in Table 1.

[0147] The experimental results regarding the capacitance and cycle efficiency for the above-described Example 1 and Comparative Examples 1 to 5 are as shown in [Table 1] below.

[0148] Example 1 Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Comparative Example 5 Storage capacity (mAh / g) 2,018 1,975 1,889 1,482 1,763 2,162 Cycle efficiency (200 cycle, %) 90 82 80 81 79 75

[0149] The method for manufacturing a silicon composite negative electrode for a secondary battery, comprising a structure in which the outer surface of hollow granules according to Example 1 is coated with carbon nanomaterials, was confirmed to have excellent capacitance and cycle efficiency when compared to the negative electrodes of Comparative Examples 1 to 5.

[0150] Specifically, in the case of Comparative Example 1, which was prepared using only ethanol excluding NMP, both the capacitance and cycle efficiency showed a tendency to decrease compared to Example 1. This is presumed to be because it became difficult to achieve uniform dispersion of the electrode active material by using only a single solvent (ethanol) instead of a mixed solvent. In a mixed solvent system, it is possible to achieve a homogeneous distribution of the active material and the formation of a uniform coating layer by utilizing the characteristics of each solvent, but when using only a single solvent (ethanol), silicon and carbon are not evenly dispersed and aggregation occurs, leading to a problem where the structural stability of the electrode is reduced.

[0151] In addition, in the case of Comparative Example 2, which was prepared using water instead of a mixed solvent or organic solvent (ethanol, NMP), the conductivity within the electrode tended to decrease and the internal resistance increased. This is presumed to be because the interaction between the water solvent and the electrode active material is different compared to organic solvents, making it difficult to achieve a uniform distribution within the electrode and preventing the coating layer from being formed homogeneously. As a result, electron movement is not smooth during the charging and discharging process, leading to an increase in the reaction resistance of the electrode, which is expected to result in a decrease in both capacitance and cycle efficiency.

[0152] In the case of Comparative Example 3, which was prepared by heat-treating a hollow spherical powder obtained by omitting the steps of preparing the second spray solution and spray-drying the second spray solution, the capacitance showed a tendency to decrease significantly (1,482 (mAh / g)) compared to Example 1. This is expected to be because silicon and carbon were not uniformly distributed due to the omission of the second spray solution preparation and second spray solution spray-drying processes, and consequently, the homogeneity of the electrode coating layer was reduced. This is because if the coating layer is not uniform, the electron movement path is not formed evenly, which causes an increase in local resistance during the charging and discharging process, and consequently, the electrochemical performance of the electrode will be degraded.

[0153] In the case of Comparative Example 4, which was manufactured by omitting the heat treatment step, it was confirmed that both the capacitance and cycle efficiency decreased compared to Example 1. This is presumed to be because the organic components of the remaining binder polymer and organic solvent were not effectively carbonized due to the omission of the heat treatment process, and consequently, the conductive carbon coating layer was not completely formed. This is because if the carbon coating layer is incomplete, the connection between the electrode active material and the conductive network weakens, and the active material gradually detaches during the charging and discharging process, which can lower the structural stability of the electrode.

[0154] In the case of Comparative Example 5, which was prepared using microsilicon with a diameter of 1 μm instead of nanosilicon, the initial capacitance increased slightly, but the long-term cycle efficiency showed a tendency to decrease significantly. This is presumed to be because as the size of the microsilicon particles increases, volume expansion intensifies during the charging and discharging process, and the mechanical stability of the electrode deteriorates. In particular, it is analyzed that the long-term cycle efficiency decreased significantly as the silicon particles rapidly cracked due to repeated charging and discharging, causing the conductive network inside the electrode to be severed and the peeling of the electrode active material to be accelerated.

[0155] Therefore, it can be confirmed that the composite cathode material produced through the manufacturing method of the present invention exhibits excellent performance in both capacitance and cycle efficiency, and it is expected to have a high potential to be utilized as a next-generation cathode material technology in the future electric vehicle battery market.

[0157] A person skilled in the art to which the present invention pertains will understand that the present invention may be implemented in other specific forms without altering its technical concept or essential features. Therefore, the embodiments described above should be understood as illustrative in all respects and not restrictive. The scope of the present invention is defined by the claims set forth below rather than by the detailed description above, and all modifications or variations derived from the meaning and scope of the claims and their equivalents should be interpreted as being included within the scope of the present invention. Furthermore, the order of operation of the configurations described in the above process does not necessarily need to be performed in a chronological order, and it is understood that even if the order of execution of each configuration and step is changed, such a process may fall within the scope of the present invention as long as it satisfies the essence of the present invention. Explanation of the symbols

[0159] S10: First spray liquid manufacturing step S20: First drying step S30: Second spray liquid manufacturing step S40: Second drying stage S50: Heat treatment step

Claims

Claim 1 A method for manufacturing a silicon composite negative electrode for a secondary battery, comprising: a first spray solution preparation step of preparing a first spray solution by adding and stirring a binder polymer and nanosilicon to a mixed solvent containing two or more organic solvents; a first drying step of spraying and drying the first spray solution to obtain a spherical powder with a hollow structure in which the nanosilicon particles are aggregated; a second spray solution preparation step of stirring the spherical powder and a commercial carbon source to prepare a second spray solution; and a second drying step of spraying and drying the second spray solution to obtain a composite of spherical powder with a hollow structure. Claim 2 The method for manufacturing a silicon composite negative electrode for a secondary battery according to claim 1 further comprises a heat treatment step of heat-treating the spherical powder composite in an inert atmosphere; and the first spray liquid manufacturing step comprises a mixed solvent manufacturing step of manufacturing a mixed solvent containing two or more organic solvents, a first stirring step of adding and stirring nanosilicon to the mixed solvent, and a second stirring step of adding and stirring a binder polymer after the first stirring step. Claim 3 A method for manufacturing a silicon composite negative electrode for a secondary battery according to claim 1 or 2, wherein the mixed solvent comprises a first organic solvent comprising one or more of NMP (N-Methyl-2-pyrrolidone), DMSO (Dimethyl sulfoxide), DMF (Dimethylformamide), and THF (Tetrahydrofuran), and a second organic solvent comprising one or more of ethanol, methanol, and acetic acid. Claim 4 A method for manufacturing a silicon composite negative electrode for a secondary battery according to claim 1 or 2, wherein the mixed solvent comprises a first organic solvent having a first boiling point and a second organic solvent having a second boiling point lower than the first boiling point. Claim 5 A method for manufacturing a silicon composite negative electrode material for a secondary battery according to claim 3, wherein the mixed solvent is characterized by the first organic solvent and the second organic solvent being mixed in a mass ratio of 10:1 to 2:

1. Claim 6 A method for manufacturing a silicon composite negative electrode for a secondary battery, characterized in that, in claim 1 or 2, the binder polymer is in an amount of 1 to 5 parts by weight per 100 parts by weight of the mixed solvent. Claim 7 A method for manufacturing a silicon composite negative electrode material for a secondary battery, characterized in that, in claim 1 or 2, the nanosilicon is in an amount of 1 to 7 parts by weight per 100 parts by weight of the mixed solvent. Claim 8 A method for manufacturing a silicon composite negative electrode material for a secondary battery, wherein, in claim 1, the nanosilicon has a size of 0.1 to 0.7 μm. Claim 9 A method for manufacturing a silicon composite negative electrode for a secondary battery according to claim 1, wherein the commercial carbon source comprises one or more of natural graphite, artificial graphite, carbon black, acetylene black, GIC (Graphite Intercalated Compound), expanded graphite, activated carbon, graphite nanoplatelets (GNP), or carbon nanotubes (CNT). Claim 10 A method for manufacturing a silicon composite negative electrode for a secondary battery according to claim 1, wherein the commercial carbon source is a carbon aqueous solution containing one or more carbons, 100 parts by weight of the carbon aqueous solution contains 0.5 to 1.5 parts by weight of one or more carbons, and the spherical powder is 4 to 6 parts by weight with respect to 100 parts by weight of the carbon aqueous solution. Claim 11 A method for manufacturing a silicon composite negative electrode material for a secondary battery according to claim 1, wherein the heat treatment step is characterized by heat treatment for 2 to 4 hours in an inert atmosphere at 600 to 800°C. Claim 12 A silicon composite anode for a secondary battery manufactured by a method for manufacturing a silicon composite anode for a secondary battery comprising a structure in which the outer surface of a hollow structure granule of any one of claims 1 to 11 is coated with a carbon nanomaterial. Claim 13 A secondary battery comprising a silicon composite negative electrode material for a secondary battery, comprising a structure in which the outer surface of the hollow structure granules of claim 12 is coated with carbon nanomaterial.